Synthesis, processing and tensile testing of a poly(l -lactide-co-caprolactone) monofilament fiber for use as an absorbable surgical suture - Sujitra Ruengdechawiwat (2018)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. A poly(l-lactide-co-caprolactone), P(LL-co-CL), 75:25 mol % copolymer was synthesized via the bulk ring-opening copolymerization of l-lactide (LL) and ε-caprolactone (CL) at 130 °C for 48 hrs. The P(LL-co-CL) copolymer obtained was characterized in terms of its molecular weight (GPC), copolymer composition (1H-NMR), monomer sequencing (13C-NMR) and thermal properties (DSC, TGA). For processing, the P(LL-co-CL) was melt spun into a monofilament fiber with fast cooling and minimal draw in order to produce an as-spun fiber that was largely amorphous and unoriented. This enabled the required oriented semi-crystalline morphology to be gradually built into the as-spun fiber in a series of controlled off-line annealing and hot-drawing steps. The final fiber, which combined sufficient tensile strength with flexibility for use as a suture material, exhibited a stress and strain at break of 344 MPa and 70%, respectively.